Adopsi Kerangka Kerja Agile Scrum untuk Meningkatkan Kompetensi Digital Guru: Sebuah Tinjauan Literatur - Miftahul a'la; Hamam Burhanuddin (Lembaga Yasin AlSys, 2026)
Although teacher digital competence (TDC) has become a focus in several previous studies, research that specifically synthesizes the adaptation of the Agile Scrum framework for systematic teacher professional development remains limited. This study aims to systematically review the literature on the adaptation of Scrum in improving teachers’ digital competence. This study used a Systematic Literature Review (SLR) approach combined with qualitative thematic analysis, involving 18 empirical studies selected through the PRISMA protocol from a total of 295 articles. The results show that core Scrum elements, such as sprints or short learning cycles, daily stand-ups, sprint reviews, sprint retrospectives, and Kanban boards, can be effectively integrated into teacher digital competence development programs. This adaptation significantly improves teachers’ Technological Pedagogical Content Knowledge (TPACK), self-efficacy, and collaborative soft skills. However, its implementation still faces challenges in the form of teacher resistance, lack of facilitator training, and limited digital infrastructure. The conclusion of the study emphasizes that Agile-TDC adaptation plays an important role in creating an iterative and collaborative professional learning environment. The implications of this study emphasize the need for policy support through the allocation of dedicated time for teacher professional development, Agile mentor training, and the provision of adequate digital infrastructure.